Erratum (Annals of Medical Research, 2025)
In the article, “Doganay D. Punctoplasty surgery combined with 22-gauge intracath intubation in punctal stenosis:A practical, cost-effective, and efficient method.” Ann Med Res. 2025;32(4):169-172, published in the April 2025issue (Vol. 32, Issue 4), the following correction has been made:The informed consent statement for Figure 1, which includes the publication of the patient's image and relatedclinical information, has been properly included at the end of the article under the "Informed Consent" sectionin the PDF version.You can access the updated article PDF file via this link:https://annalsmedres.org/index.php/aomr/article/view/4830